EFFECT OF GAMMA RADIATION ON SOME DOSIMETRIC INTEREST COMPOUNDS: AN EPR STUDY - BÎRLEA, Vlad; PETRIȘOR, Dina Mariana; DAMIAN, Grigore (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The present research was undertaken in order to investigate if some compounds used as natural sweeteners (steviol and sucrose) can be used as EPR dosimeters. The samples were exposed to low doses of gamma ionizing radiation used in the practices of radiodiagnostic medicine and interventional radiology. The EPR spectra of the gamma irradiated compounds reveal large signals, with multiple lines, which are characteristic for the free radicals in the solid state. From the analysis of the dependence of EPR signal of the absorbed dose, it was observed that by γ-irradiation the amount of generated radicals shows a linear dependence, which mean that there exist a possibility to use these two compounds as EPR dosimeters.